Antiretroviral Therapy Adherence Enhancing Interventions for Adolescents and Young Adults 13–24 Years of Age: A Review of the Evidence Base. (1st August 2016) - Shaw, Sarah; Amico, K. Rivet
Abstract : Introduction: Youth living with HIV are highly under-represented in the evidence base for adherence interventions, despite their diverse and unique needs and barriers. Objective: This systematic review aimed to identify antiretroviral therapy (ART) adherence interventions specifically targeting adolescents and young adults (defined as ages 13–24) with the goal of characterizing the evidence base. Methods: Articles were identified using the PubMed database and cover work published through September 14, 2015. Inclusion criteria: (1) average age 13 to 24, (2) HIV positive, (3) on or beginning ART, (4) intervention targeted ART adherence in full or in part, (5) reported adherence, viral load, and/or CD4 count outcomes. Strength of evidence was defined as level 1 [randomized controlled trial (RCT) with significance testing on outcomes], 2 (within group studies with statistical testing on outcomes), 3 (RCTs with descriptive results), or 4 (within group studies with descriptive results). Results: Of 151 articles, 10 met inclusion criteria. Published between 2003 and 2014, these studies evaluated diverse intervention approaches. Most were conducted in the US and were small pilots that have yet to be replicated despite promising results. Only 3 studies met criteria for highest level strength of evidence; 2 supported a phone-based counseling approach with adherence monitors and 1 for weekly individual and family counseling. Conclusions: Despite nearly 20 years passing since the wide-scale availability of ART, and clear recognition that adolescents and youth adults fair worse on the cascade of HIV care, the evidence base remains sparse and underdeveloped. Promising approaches need replication and more rigorous studies are desperately needed.